Analisis Strategi Pemasaran Agen dalam Mempertahankan Loyalitas Nasabah di PT BRI Life Syariah Cabang Gatot Subroto - Muhammad Risalah Harahap; Rahmi Syahriza (Universitas Muhammadiyah Enrekang, 2022)
Bri Life Syariah branch of Gatot Subroto is one of the companies engaged in insurance. In an effort to increase sales of insurance policies in Medan City generally use several marketing strategies. The marketing strategy is implemented by the insurance agent/consultant of the company. This type of research is descriptive with a qualitative approach. Data collection used by using interviews, study documentation and observation. The study in this research is to find out